Participatory Safety Improvement in Informal MSMEs: Human Factors, Environmental Risks, and WISE Intervention Outcomes in Indonesia - Siregar, Khoirotun Najihah; Amalia, Nur; Apriliana, Ananda; Telamumbanua, Ervan Kristin (Hasanuddin Medan, 2025)
Occupational health and safety in the informal Micro, Small, and Medium Enterprises (MSME) sector remains a critical yet under-examined issue in Indonesia. This qualitative case study investigates the determinants of workplace accidents in the Panglong Kayu Kanalom wood-processing industry in Medan, focusing on human and environmental factors. Data were collected through triangulated methods including in-depth interviews, field observations, and documentation, with analysis structured using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) framework. The findings reveal that 80% of participants did not use personal protective equipment (PPE), and all respondents lacked formal safety training. Unsafe behaviors, habitual risk-taking, and normalization of hazards were prevalent among long-term workers. Environmental risks such as poor ventilation, high noise exposure, disorganized machinery layout, and airborne sawdust were found to significantly impair worker safety and cognitive concentration. The implementation of a participatory WISE (Work Improvement in Small Enterprises) training program demonstrated significant behavioral and knowledge improvements. PPE usage increased from 20% to 73%, and awareness of occupational hazards rose to 88%. The application of the HIRARC matrix proved instrumental in prioritizing risks and achieving quick safety improvements, even within the constraints of informal MSMEs. The study supports the effectiveness of participatory, theory-informed safety interventions and calls for their wider application in similar contexts. These findings offer actionable insights for policymakers and practitioners aiming to improve occupational safety in Indonesia’s informal sector.